2011
DOI: 10.1510/icvts.2010.265165
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative computed tomography is associated with lower risk of perioperative stroke in reoperative cardiac surgery

Abstract: Preoperative computed tomography (CT) use appears to be increasing among patients undergoing cardiac reoperations. We hypothesized that preoperative CT imaging reduces adverse outcomes and operative mortality for these patients. From July 2002 to February 2009, 373 patients underwent cardiac reoperations. Patients were stratified according to those with preoperative CT imaging (CT, n=140) and to those without preoperative CT imaging (NCT) (NCT, n=233). Preoperative risk, operative features, and postoperative o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…According to the comparison between the operation results of the patients and the previous CT results, if they are consistent, they are true positive, if not, they are false positive. Categorical variables were compared using either Pearson's chi-squared test or Fisher's exact tests, and continuous variables were compared by Student's t -test for normally distributed data or Mann-Whitney's U -test for non-normally distributed data where appropriate [ 10 ]. All categorical variables were expressed as percentage within the group, and continuous variables were expressed as mean ± standard deviation (S.D.)…”
Section: Methodsmentioning
confidence: 99%
“…According to the comparison between the operation results of the patients and the previous CT results, if they are consistent, they are true positive, if not, they are false positive. Categorical variables were compared using either Pearson's chi-squared test or Fisher's exact tests, and continuous variables were compared by Student's t -test for normally distributed data or Mann-Whitney's U -test for non-normally distributed data where appropriate [ 10 ]. All categorical variables were expressed as percentage within the group, and continuous variables were expressed as mean ± standard deviation (S.D.)…”
Section: Methodsmentioning
confidence: 99%
“…Performing a CTA prior to re-do cardiac surgery, with extra-cranial coverage to include the origin of the internal mammary arteries, allows identification of the location and can help surgeons alter surgical strategy, reducing the risk of intra-operative injury and improve outcomes [ 80 , 81 ].…”
Section: Notes On Specific Protocolsmentioning
confidence: 99%
“…This analysis suggests that a history of previous cardiac surgery does not independently confer a significant incremental risk of operative mortality, but that patients with greater number of previous operations appear to be at higher risk." 1(p2) Several strategies for risk reduction in mortality and morbidity during resternotomy are described 8 : Polytetrafluoroethylene membrane, 3 preoperative chest computed tomography (CT), [9][10][11][12] use of an oscillating saw, 10,13 and peripheral cannulation. 10,11,14 The aim of this study was to describe the experience in reoperation of pediatric patients with congenital heart disease (CHD) in a center from a low-middle-income country and to determine the factors associated with operative mortality.…”
Section: Ctmentioning
confidence: 99%
“…1 Many centers use preoperative CT in a routine manner or in high-risk patients to develop a surgical plan in order to decrease the probability of cardiac injury during repeat sternotomy. [9][10][11][12] However, this type of preoperative evaluation increases the costs of each procedure and in a health system with limited resources such as ours, it represents an additional cost that is difficult to afford. In this study, we found that preoperative CT is not always necessary to achieve good results, using only a preoperative chest X-ray and angiogram to assess the relationship between cardiac structures and the sternum.…”
Section: Commentmentioning
confidence: 99%